Mathematical Model for the Transmission Dynamics of Malaria in Kabale Municipality. - Nabasa, Moses (Kabale University, 2024)
The purpose of this study was to develop a mathematical model for the transmission dynamics of malaria in western Uganda. Malaria remains one of the most prevalent and lethal human infections worldwide. It is caused by the protozoan Plasmodium, transmitted to vertebrates by female genus Anopheles mosquitoes when they feed on blood. The mathematical model was developed based on SIER. The disease-free equilibrium, Xo for mosquitoes is obtained in the absence of the disease. A malaria model was developed and analyzed to study the stability of both disease-free and endemic equilibrium points. Using the matrix generation approach, the basic reproduction number R0 was computed. Therefore, the disease-free equilibrium of the model obtained is both locally and globally stable for R0<1. It is also shown that the endemic equilibrium solution of the model is globally asymptotically stable if R0>1.